Contribution of Nlrp3 Inflammasome Activation Mediated by Suilysin to Streptococcal Toxic Shock-like Syndrome - Song, Liqiong; Li, Xianping; Xiao, Yuchun; Huang, Yuanming; Jiang, Yongqiang; Meng, Guangxun; Ren, Zhihong (Frontiers in Microbiology, 2020)
Objective The aim of this study was to investigate the molecular mechanism of inflammasome activation in response to Streptococcus suis serotype 2 (SS2) infection and its contribution to the development of Streptococcal Toxic Shock-like Syndrome (STSS). Method To verify the role of suilysin (SLY) in STSS, we infected bone-marrow-derived macrophages (BMDMs) in vitro and C57BL/6J mice intraperitoneally with the SS2 wild-type (WT) strain or isogenic sly mutant (∆SLY) to measure the IL-1β release and survival rate. To determine the role of inflammasome activation and pyroptosis in STSS, we infected BMDMs from WT and various deficient mice, including Nlrp3-/-, Nlrc4-/-, Asc-/-, Aim2-/-, Caspase-1/11-/-, Gsdmd-/- ex vivo and intraperitoneally injected WT, Nlrp3-/-, Caspase-1/11-/-, and Gsdmd-/- mice with SS2, to compare the IL-1β releases and survival rate in vivo. Results The SS2-induced IL-1β production in mouse macrophages is mediated by SLY ex vivo. The survival rate of WT mice infected with SS2 was significantly lower than that of mice infected with the ∆SLY strain in vivo. Furthermore, SS2-triggered IL-1β releases, and the cytotoxicity in the BMDMs required the activation of the Nlrp3, Caspase-1/11, and Gsdmd inflammasomes, but not the Nlrc4 and Aim2 inflammasomes ex vivo. The IL-1β production and survival rate of WT mice infected with SS2 were significantly lower than those of the Nlrp3-/-, Caspase-1/11-/-, and Gsdmd-/- mice in vivo. Finally, the inhibitor of the Nlrp3 inflammasome could reduce the IL-1β release and cytotoxicity of SS2-infected macrophages ex vivo and protect SS2-infected mice from death in vivo. Conclusion Nlrp3 inflammasome activation triggered by SLY in macrophages played an important role in the pathogenesis of STSS.